Knowledge transfer process in Perak's small medium enterprises (SME) companies / Syajurratuddur Mohd Saleh. - Mohd Saleh, Syajurratuddur (Universiti Teknologi MARA Cawangan Selangor, 2017)
Knowledge transfer (KT) exists in every corner of SME, in its structure and relationship especially in its people. Even though knowledge management will benefit SME as they are rich of tacit and explicit knowledge but lacking in expertise. Currently, knowledge management (KM) is almost impossible for Small and Medium Enterprise (SME). Since SME have efficient and informal communication network, knowledge transfer and sharing is essential especially in an organization with limited resources. Therefore, in the wake of knowledge-based economy, knowledge transfer and sharing is the best tool for SME in enhancing competence and organizational performance which relate its needs and background. Knowledge transfer and sharing is still at new especially in SME.The objective of this study is to exploring the knowledge transfer process in Small and Medium Enterprise (SME) businesses in Perak. In doing this, it examines how knowledge is transferred in SME businesses between people in the company. The study also explores problems and factors affecting knowledge transfer process. The knowledge transfer framework is proposed to assist SME managers in formulating and implementing for knowledge transfer process. By using a qualitative research approach, this research employed a case study approach with multiple cases strategy. Two SME company in Perak were used as cases. The study used semi- structured interviews with SME managers, workers and information provider in Perak state. The interview results were analyzed across the cases and the findings were used to test and refine the proposed framework. The main findings from these two interviewed revealed that the knowledge transfer process is most affected by communication, trust, relationship, willingness, experience and organization culture. However, the finding also revealed the major problem in the process such as language and technology.